Immune activation in HIV infection: what can the natural hosts of simian immunodeficiency virus teach us?. Issue 2 (March 2016) - Ploquin, Mickaël J.; Silvestri, Guido; Müller-Trutwin, Michaela
Abstract : Purpose of review: The review summarizes studies in natural hosts, with a particular focus on the control of immune activation and new insights into viral reservoirs. We discuss why these findings are relevant for HIV research today. Recent findings: AIDS resistance in natural hosts is characterized by a rapid control of inflammatory processes in response to simian immunodeficiency virus infection despite persistent viremia. Although CD4 + T cells are dramatically depleted in the intestine in primary infection, interleukin 17-producing T helper cells (Th17) are preserved and natural hosts lack microbial translocation. Thus, viral replication in the gut is not sufficient to explain mucosal damage, but additional factors are necessary. Natural hosts also display a lower infection rate of stem-cell memory, central memory and follicular helper T cells. The follicles are characterized by a lack of viral trapping and the viral replication in secondary lymphoid organs is rapidly controlled. Hence, the healthy status of natural hosts is associated with preserved lymphoid environments. Summary: Understanding the underlying mechanisms of preservation of Th17 and of the low contribution of stem-cell memory, central memory and follicular helper T cells to viral reservoirs could benefit the search for preventive and curative approaches of HIV. Altogether, the complementarity of the model helps to identify strategies aiming at restoring full capacity of the immune system and decreasing the size of the viral reservoirs.